Seven steps to mastering business analysis : the essentials - Champagne, Jamie, 1982- (USA : J. Ross Publishing ., 2020)
"This volume in the Business Analysis Professional Development Series by leading expert and keynote speaker Jamie Champagne is the second edition of our number #1 best seller. It is an instructional text that will help relatively new analysts, and those expected who do business analysis work in addition to their main role, build their skill sets, master the essentials, and advance their careers. Since the content is aligned with the consensus-based business analysis standards of both the Project Management Institute (PMI) and the International Institute of Business Analysis (IIBA), as articulated in their respective guides and bodies of knowledge, this book continues to be an excellent reference for the PMI-PBA, ECBA, CCBA, and CBAP certification exams"--
Revised edition of Seven steps to mastering business analysis, c2009.
Includes bibliographical references and index.
Keywords: Business analysts; Business planning; Organizational effectiveness; Business Environment; Requirements analysis Techniques